Bimbingan Teknis Peningkatan Keterampilan Aparatur Pemerintah Desa di Kecamatan Pammana Kabupaten Wajo - Nawawi, Juanda; Anwar, Sakaria To; Sabiq, Muhammad; Muhammad, Sawedi; Arisnawawi, Arisnawawi; Wanti, Andi Rewo Batari (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2022)
The concept of local self-governance places the village in an autonomous position in making and implementing village policies, so that this condition implies an increase in the capabilities and skills of the village apparatus in empowering the community in their village. The role played by village government officials in Pammana District, Wajo Regency is very important but has not been supported by adequate capabilities. In general, the ability of the village government apparatus in Wajo Regency has not been maximized in supporting the ongoing development process, especially in the community empowerment program. This fact has implications for the process and results of development that occurs in the village. Currently, the community empowerment process in Pammana District, Wajo Regency has been carried out by adhering to the bottom up principle. The district government carries out a Development Planning Deliberation (Musrembang) mechanism, including community empowerment programs starting from the village level as material for formulating empowerment and development programs in Wajo Regency as a whole. However, because the village government apparatus does not have adequate capabilities and skills in playing its role as a catalyst for development and community empowerment, development and empowerment in the village is less than optimal. Seeing the problems related to the not yet maximal role of the village government apparatus in planning and implementing empowerment development in the village, efforts were made to further improve the community empowerment capacity of the village government apparatus. A good level of quality planning and development management is needed for village government officials, in the form of capacity building through socialization and training. Through a series of empowerment activities, it can encourage accountable and transparent village governance and produce village apparatus cadres who have good knowledge, attitudes and skills in implementing development, especially community empowerment programs. With the quality of development planning that has been good in the region, so that it takes place better according to the conditions and needs of the region